Effectiveness of Project-Based Inquiry Learning in Developing HOTS-Based Scientific Literacy: Moderated by Science Process Skill - Rajagukguk, Kiki Pratama; Suyanti, Retno Dwi; Saragih, Abdul Hasan; Sinclair Taylor, Peter Charles (FKIP Universitas Lampung, 2025)
Effectiveness of Project-Based Inquiry Learning in Developing HOTS-Based Scientific Literacy: Moderated by Science Process Skill. Objectives: This study examines three core questions: (1) whether the Project-Based Inquiry (PBI) model improves students’ HOTS scientific literacy, (2) whether students’ initial Science Process Skills (SPS) influence their outcomes, and (3) whether there is an interaction between the two. These variables were selected because HOTS-based scientific literacy and SPS are essential competencies for prospective elementary teachers. Methods: A quasi-experimental design was used with two naturally formed groups. The experimental group learned through the project-based inquiry model, while the control group used guided inquiry. Data were collected using a project assessment sheet and the HOTS scientific literacy test, with identical pre- and post-tests administered. The data were analyzed using: 1) Normality and homogeneity test, 2) Paired sample t-test, 3) Independent sample t-test, and 4) Hypothesis testing was carried out using two-way ANOVA, where H₀ was rejected if the significance value was <0.05. Findings: The analysis for the learning model factor yielded a highly significant result (p = 0.000; < 0.05). The results show that the learning model had a significant effect on HOTS scientific literacy, with the PBI model outperforming guided inquiry (p = 0.000). SPS level did not produce a significant independent effect (p = 0.562), and no interaction was found between the learning model and SPS. These findings indicate that the PBI model is the primary factor driving students’ improvement. Conclusion: Overall, Project-Based Inquiry is an effective approach to strengthening HOTS scientific literacy among prospective elementary teachers. Although SPS levels did not independently influence outcomes, students across SPS levels still benefited from PBI. These findings offer theoretical insight into how inquiry–project learning supports higher-order reasoning and provide practical guidance for developing instructional designs that foster analytical and evidence-based thinking in teacher education programs. Keywords: project-based inquiry, guided inquiry, science process skill, hots, scientific literacy, science education.